Analyzing English Politeness Main Character Thank You, Sorry, Please in “Hati Suhita” By Khilma Anis - Andayani, Tri; Siti Asyah; Sulistyaningsih, Sulistyaningsih; Wahyuni, Farida Eka (International Journal of English and Applied Linguistics (IJEAL), 2024)
The purpose of this study is to describe the analysis of English politeness main character: thank you, sorry, and please in the novel "Suhita's Heart" contains the account politeness main character. The method used in this study is qualitative descriptive because the results will be described clearly. The data source uses students studied in the novel "Hati Suhita". The data was taken from the analysis of interviews and notes from the "Hati Suhita" novel. The instrument is the researcher's self, the article "Heart of Suhita", tables, notes, and interviews, which will be used to identify the part of English politeness. The findings of the answer to the objectives of this study are: 1) the word sorry by 90%, as many as 11 words of apology used by the character Alina are 10 words of apology, the others are not the main character who mentions the dialogue of apology and the word asking for help by 100%, there is only 1 word, please. In the context of teaching compensation forms such as "thank you," "sorry," and "please," Alina Suhita, as an educator in a pesantren (Islamic boarding school), would likely incorporate several pedagogical strategies. There are Role modeling, Explicit Teaching, Role-Playing Activities, Reflective Practices, Positive Reinforcement, Integration into Daily Activities, and Cilturaly relevant context The results of this study can advance cross-cultural communication research and offer readers a deeper understanding of the importance of civility in communication.